Predicting the Indonesian sustainable marketing communication on 2023 trends - Diawati, Prety; Mutalov, Islam C.; Kasmi, Mauli; Abdullah, Akmal; Yuliastuti, Hilda (Faculty of Communications Science, Dr. Soetomo University, 2023)
After being hit by the Covid 19 pandemic, Indonesia is still trying to rise from the economic downturn, especially with the many paralysed microbusinesses. Perspective updates have also weakened because of activity restrictions during the pandemic. Before the pandemic, the macro film industry was rapidly growing. Now, it is the turn of the microfilm industry to rise due to new ways of promotion without incurring expensive production costs. The role of sustainable marketing is needed to achieve this target for 2023. The Systematic Literature Review was used as the methodology to analyse the data in this research. The results show that the influencer marketing industry and the influencer agencies depend on social media.